Prevalence and resistance pattern of uropathogens from community settings of different regions: an experience from India. Issue 2 (9th February 2022) - Mohapatra, Sarita; Panigrahy, Rajashree; Tak, Vibhor; J. V., Shwetha; K. C., Sneha; Chaudhuri, Susmita; Pundir, Swati; Kocher, Deepak; Gautam, Hitender; Sood, Seema; Das, Bimal Kumar; Kapil, Arti; et al.
Abstract : Introduction. Urinary tract infection (UTI) is one of the most common infections in clinical practice worldwide in both healthcare and community settings causing significant morbidity and mortality. It is one of the major conditions at the community level treated empirically and regarded as a potential cause of emergence of antimicrobial resistance (AMR). Limited information is available regarding community-acquired UTI (CA-UTI) from India. Methodology. This is a first of its kind, multicentric-cross-sectional study at the community level targeting patients attending the out-patient department (OPD) of the community health centre (CHC) from four geographical regions (North, South, West and East) of India. The study had been designed to determine the epidemiology, antibiogram profile and identification of extended-spectrum beta-lactamase (ESBL) producer and carbapenem resistant (CR) uropathogens. Samples were collected prospectively from UTI suspected patients coming at CHC and processed at the tertiary healthcare centres using a common standard operating procedure. Clinical history of all the patients exhibiting significant bacteriuria was collected and data was analysed. Result. Overall, 250 out of a total of 2459 (10.1 %) urine samples were positive for bacteria with significant bacteriuria (adult: paediatrics, 6.7 : 1). Females were predominantly affected (male: female, 1 : 2.9). History of recent episode of UTI was observed as the commonest risk factor followed by diabetes mellitus. Altogether, 86 % of total cases were caused by Escherichia coli (68 %) and Klebsiella pneumoniae (17.6 %) together. Among the commonly used oral antibiotics for the Gram-negative bacilli (GNB), the highest resistance was observed against beta-lactams, first- and second-generation cephalosporins, fluoroquinolones and co-trimoxazole. Overall, the prevalence of ESBL producer and CR isolates were 44.8, and 4.3 %, respectively. However, the ESBL production, CR and nitrofurantoin resistance among the uropathogenic E. coli (UPEC) isolates was 52.8, 5.1 and 14 %, respectively. No resistance was found against fosfomycin among the UPEC isolates. Conclusion. The current study highlights the increasing incidence of AMR among uropathogens at the community-settings of India. A significant percentage of ESBL producers among the isolated UPEC and K. pneumoniae were observed. The currently available evidence supports the clinical recommendation of fosfomycin and nitrofurantoin for empiric therapy in CA-UTI in India.